Efficient grain refinement of as-cast Al-Mg-Si alloy via warm deformation: grain boundary based quantitative analysis on its dynamic recrystallization behaviors - Jiawei Luo; Jin Zhang; Wei Xiong (Materials & Design)
Industrial production of fine-grained Al-Mg-Si alloys usually involves homogenization of cast ingots and deformation at extreme conditions (temperature, force). This work demonstrates a more efficient route, where the as-cast 6xxx Al-Mg-Si alloys achieve superior grain refinement (5.43 ± 5.7 µm) compared to homogenized samples (17.13 ± 22.1 µm) at warm deformation temperature (270℃). Moreover, non-closed high-angle grain boundaries (HAGBs) and closed-loop HAGBs, which respectively represent the continuous dynamic recrystallization (CDRX) and discontinuous dynamic recrystallization (DDRX), are identified and statistically analyzed. Results show that the as-cast Al-Mg-Si alloy activated CDRX and DDRX more rapidly than its homogenized state at warm deformation temperatures, TEM observations have revealed that this was caused by elemental segregation along grain boundaries, which reduces grain boundary energy and thus facilitates recrystallization nucleation, additionally, it consumes a significant amount of solute atoms and facilitates the CDRX at grain interiors. In contrast, the HG-AlMgSi contains high amount of nano-precipitates which hinders dislocation motion, suppressing CDRX. This study offers new insights into the dynamic recrystallization behavior of as-cast and homogenized Al-Mg-Si aluminum alloy at warm deformation temperatures and highlights the potential of rapid production method of fine-grained aluminum alloys.